2014
DOI: 10.3171/2014.4.spine13545
|View full text |Cite
|
Sign up to set email alerts
|

Electrophysiological evidence of functional improvement in the corticospinal tract after laminoplasty in patients with cervical compressive myelopathy

Abstract: Object Cervical laminoplasty is a surgical procedure for cervical compressive myelopathy (CCM), and satisfactory outcomes have been reported. However, few reports have examined the pathophysiology of improvements in spinal cord function. The aim of this study was to investigate the variation in central motor conduction time (CMCT) before and after cervical laminoplasty in patients with CCM. Methods Motor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 37 publications
2
12
1
Order By: Relevance
“…The type III, IV, and V MEPs baseline can often gradually reflect the severity of clinical symptoms. Some previous study also showed a correlation between the mJOA score and the electrophysiological parameters in CCM [7,18,19,46]. Moreover, according to this study and previous report [47], the cervical cord morphology and electrophysiological parameters are also relevant in CCM.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…The type III, IV, and V MEPs baseline can often gradually reflect the severity of clinical symptoms. Some previous study also showed a correlation between the mJOA score and the electrophysiological parameters in CCM [7,18,19,46]. Moreover, according to this study and previous report [47], the cervical cord morphology and electrophysiological parameters are also relevant in CCM.…”
Section: Discussionsupporting
confidence: 85%
“…It is important to assess cervical cord function in patients with CCM during surgical treatment. Over the past decades, the majority of studies are concerning the application of intraoperative transcranial motor evoked potential (MEP) to detect impending spinal cord damage, early warning the operating team to take action to avoid injury in cervical spine surgery [2][3][4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…Correlations between CMCT and the JOA score have been reported. 31,37 However, our results showed no correlation between the JOA score and CMCT in the CCM-DM group. In the CCM-DM group, the JOA score correlated with the MEP-AH and PCT-AH before and after surgery, while the JOA score before surgery correlated with the CMCT and MEP values in the CCM group.…”
Section: Discussioncontrasting
confidence: 53%
“…37 CMCT values improved after cervical laminoplasty with significant correlations to the JOA score before and after surgery. 31 Moreover, sufficient clinical results have been reported even in myelopathy patients older than 80 years, provided the patients are selected correctly through electrophysiological evaluation via MEP and CMCT study. 38 However, those studies excluded diabetic patients or did not clearly mention the patients with DM.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to our result in CCM, previous study also proved a correlation between the JOA score and the electrophysiological parameters. 11 Therefore, we can assert that there are significant correlations among cervical cord morphology, electrophysiological parameters, and JOA score.…”
Section: Discussionmentioning
confidence: 98%